Thermal limits in relation to acclimation in the neotropical millipede Gymnostreptus olivaceus (Diplopoda, Spirostreptidae) - Boccardo, Lilian; Penteado, Carlos Henrique Silva [UNESP] (Taylor & Francis, 1998)
The neotropical millipede, Gymnostreptus olivaceus, lives at ambient temperatures of about 20°C. Its thermal tolerance was tested after acclimation to lower and higher temperatures as occurs under winter and summer conditions in the south and southeast regions of Brazil. An increase in tolerance to low temperatures was found in adapted specimens. The ecological aspects of this capability are discussed.
Keywords: Acclimation; Brazil; Gymnostreptus olivaceus; Millipedes; Temperature tolerance; Thermal limits